Genre Features of Jamal Kemal's Epics - Nazarova Dildora (Researchparks Publishing, 2021)
An important feature of Jamal Kemal's work is that he appears in our poetry with equal aruz, finger and free genre. The same can be said of his epics. Consequently, the poet's epics are dominated by tradition. In particular, in the